2000
DOI: 10.1055/s-0037-1614052
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of von Willebrand Factor by Endothelial Cells

Abstract: SummaryThe haemostatic activity of plasma von Willebrand factor (vWF) is a function of multimer size. Only the large vWF multimers are effective in promoting platelet adhesion to a site of vascular injury. We observed that the conditioned medium of cultured human umbilical vein, human microvascular and bovine aortic endothelial cells contained an activity which reduced the average multimer size of plasma or purified vWF. The average multimer size of vWF produced endogenously by human umbilical vein endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
1
39
1
Order By: Relevance
“…Von Willebrand factor forms huge multimers connected via disulfide bonds. Its biological activity is known to depend on multimer size and reductase secreted from endothelial cells downsizes the multimer (37). Significant changes in multimer distributions of adiponectin with meals were not seen in our preliminary experiments, though Pajvani et al (29) recently reported a shift to smaller multimers to occur with insulin administration.…”
Section: Table IIIcontrasting
confidence: 57%
“…Von Willebrand factor forms huge multimers connected via disulfide bonds. Its biological activity is known to depend on multimer size and reductase secreted from endothelial cells downsizes the multimer (37). Significant changes in multimer distributions of adiponectin with meals were not seen in our preliminary experiments, though Pajvani et al (29) recently reported a shift to smaller multimers to occur with insulin administration.…”
Section: Table IIIcontrasting
confidence: 57%
“…15 Endothelial cells in culture secrete an activity that reduces the size of very large multimers of von Willebrand factor (VWF). 16 This activity appears to be independent of the proteolysis of VWF by ADAMTS13 and is inhibited by thiol blocking reagents. The VWF reductant secreted from endothelial cells has been identified as thrombospondin-1.…”
mentioning
confidence: 95%
“…However this static view of the function of disulfide bonds has been challenged since the mid1990s by a steady increase of evidence for extracellular regulation due to disulfide cleavage. Examples include secreted proteins like thrombospondin-1 [122], von Willebrand factor [123,124] and plasmin [125], and cell surface receptors like the CD-4 T-cell receptor [126], integrins [127,128] and the HIV protein gp120 [129]. Extracellular redox regulation has also been suggested as essential in activation of Gprotein coupled receptors [130].…”
Section: Chemistry Controls Mechanics: Mechanochemical Switches In Thmentioning
confidence: 99%